Saluran Pemasaran Belimbing Organik (Averrhoa carambola L.) pada Kelompok Tani Sekar Sari Subak Mambal, Desa Mambal, Kecamatan Abiansemal Kabupaten Badung - SAGUNG DWIYANTI INDRASWARI; I KETUT SUAMBA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
Abstract Marketing Channel of Belimbing Organic (Averrhoa carambola L.) at Sekar Sari Farmer’s Group of Subak Mambal, Mambal Village, Abiansemal District Badung Regency Marketing is economic activity which distributes goods from producen to consumen. Marketing aspect of Belimbing is the most important thing in supporting increase the result of Belimbing production. Many of institution involved in marketing will influence short and long of marketing chain and volume of marketing cost. The volume of marketing cost will direct to as big as the different of the price between producen and consumen. The purpose of this research want to know the marketing channel which is used by the farmer, the volume of marketing margin and farmer’s share, and the most effisientic of marketing channel. The data which used in this study is qualitative and quantitave. The analysis data is descriptively toward marketing channel by supporting simple tabulation of using marketing margin formula, farmer’s share and marketing efficiency. The result of this research showed there are three marketing channel. The first marketing channel is obtained marketing margin about IDR 14.000 with farmer’s share 41,67% and efficiency percentage is got 27,12% based on the cost and 31,20% based on the profit. The second marketing channel is obtained marketing margin about IDR 4.000 with farmer’s share 71,42% and efficiency percentage is got 11,04% based on the cost and 17,53% based on the profit. The third marketing channel with zero margin and farmer’s share 100% and efficiency percentage based on the cost and the profit is got zero percent. Keyword: Marketing, Margin, Efficiency of Marketing Channel